First-order necessary conditions in locally Lipschitz multiobjective optimization. (2nd September 2018) - Constantin, Elena
Abstract: In this paper, some nonsmooth analogues of the Burachik–Rizvi regularity conditions are introduced for a nonsmooth multiobjective optimization problem with equality and inequality constraints and with an arbitrary set constraint. Primal first-order necessary conditions for local efficiency and local Geoffrion-proper efficiency are given for this problem. Dual Kuhn–Tucker necessary conditions for local efficiency and local Geoffrion-proper efficiency are obtained for the multiobjective problem with equality and inequality constraints.